Thermally deformed NdFeB magnet and preparation method thereof

By mixing the iron-nickel alloy powder with the neodymium iron boron fast quenching powder under vacuum and subjecting to hot pressing and thermal deformation, the problem of poor orientation of the hot-deformed neodymium iron boron magnet is solved, and its remanent magnetic and magnetic energy is significantly improved It simplifies the process and is suitable for industrial production.

CN114883105BActive Publication Date: 2024-12-31NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210509071.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-11
Publication Date
2024-12-31
Estimated Expiration
2042-05-11

AI Technical Summary

Technical Problem

The traditional thermally deformed neodymium iron boron magnet has poor orientation, resulting in low residual magnetism. The existing improvement methods are complex in technology and are not suitable for industrial production.

Method used

Under vacuum conditions, the iron-nickel alloy powder containing nickel elements is mixed with neodymium iron boron quick quenching powder and subjected to hot pressing and thermal deformation. The nickel elements are distributed at the Nd-Fe-B grain boundaries and strips to enhance the crystal. The exchange and coupling between particles improves magnetic performance.

Benefits of technology

It significantly improves the residual magnetic and magnetic energy production of thermally deformed neodymium iron boron magnets, simplifies the process flow, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003638549410000111
    Figure BDA0003638549410000111
  • Figure BDA0003638549410000121
    Figure BDA0003638549410000121
  • Figure HDA0003638549420000011
    Figure HDA0003638549420000011
Patent Text Reader

Abstract

The present invention relates to a hot-deformed NdFeB magnet and a preparation method thereof. The preparation method of the hot-deformed NdFeB magnet comprises the following steps: providing an iron-nickel alloy powder, wherein the mass fraction of the nickel element in the iron-nickel alloy powder is greater than or equal to 15%; and providing NdFeB quick-quenching powder, mixing the NdFeB quick-quenching powder with the iron-nickel alloy powder to obtain a mixed powder, and hot pressing and hot-deforming the mixed powder under vacuum conditions to obtain a hot-deformed NdFeB magnet, wherein the mass fraction of the iron-nickel alloy powder in the mixed powder is less than or equal to 3%. The preparation method of the hot-deformed NdFeB magnet can effectively improve the remanence and magnetic energy product of the hot-deformed NdFeB magnet, thereby optimizing the magnetic properties of the hot-deformed NdFeB magnet, and the process is simple, and can be widely used in the actual production of hot-deformed NdFeB magnets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rare earth permanent magnetic materials, in particular to a thermally deformed NdFeB magnet and a preparation method thereof. Background Art

[0002] NdFeB materials have the characteristics of uniform magnetic properties, high corrosion resistance, vibration resistance and impact resistance, so they have huge market value in the fields of wind power generation and electronic products. Among them, compared with sintered NdFeB, hot-deformed NdFeB magnets have technical advantages such as less rare earth usage, shorter process flow, lower processing temperature, near-net forming and high material yield, and have greater market competitive advantages in the preparation of special-shaped magnets such as magnetic rings.

[0003] Traditionally, hot-deformed NdFeB magnets are oriented by plastic deformation. However, due to the uneven composition and force of each part of the NdFeB magnet during the hot deformation process, the grains are arranged irregularly, resulting in poor orientation of the hot-deformed NdFeB magnet, and thus low remanence of the hot-deformed NdFeB magnet. Although the magnetic properties of hot-deformed NdFeB magnets can be improved by coating or electroplating soft magnetic materials on the surface of NdFeB quick-quenching powder by combining soft magnetic materials and permanent magnetic materials, this method has limited effect on improving the remanence and magnetic energy product of hot-deformed NdFeB magnets, and the process is complicated and not suitable for industrial production. Summary of the invention

[0004] Based on this, it is necessary to provide a thermally deformed NdFeB magnet and a preparation method thereof to address the above problems; the preparation method of the thermally deformed NdFeB magnet can effectively improve the remanence and magnetic energy product of the thermally deformed NdFeB magnet, thereby optimizing the magnetic properties of the thermally deformed NdFeB magnet, and the process is simple, and can be widely used in the actual production of thermally deformed NdFeB magnets.

[0005] A method for preparing a thermally deformed NdFeB magnet, the method comprising the following steps:

[0006] Providing an iron-nickel alloy powder, wherein the mass fraction of nickel in the iron-nickel alloy powder is greater than or equal to 15%; and

[0007] Provide NdFeB quick-quenching powder, mix the NdFeB quick-quenching powder with the iron-nickel alloy powder to obtain a mixed powder, and perform hot pressing and hot deformation treatment on the mixed powder under vacuum conditions to obtain a hot-deformed NdFeB magnet, wherein the mass fraction of the iron-nickel alloy powder in the mixed powder is less than or equal to 3%.

[0008] In one of the embodiments, the iron-nickel alloy powder further contains cobalt element, and the mass fraction of the cobalt element in the iron-nickel alloy powder is less than or equal to 20%.

[0009] In one of the embodiments, the mass fraction of the cobalt element in the iron-nickel alloy powder is 10%-20%.

[0010] In one of the embodiments, the mass fraction of the nickel element in the iron-nickel alloy powder is 15%-28%.

[0011] In one of the embodiments, the mass fraction of the iron-nickel alloy powder in the mixed powder is 1%-3%.

[0012] In one embodiment, the average particle size of the iron-nickel alloy powder is less than 5 μm.

[0013] In one embodiment, before the step of mixing the NdFeB quenching powder with the Fe-Ni alloy powder, the Fe-Ni alloy powder is subjected to a deoxidation pretreatment.

[0014] In one embodiment, the hot pressing temperature is 600°C-700°C, the pressure is 3MPa-6MPa, and the vacuum degree is greater than or equal to 5×10 -2 Pa;

[0015] And / or, the thermal deformation temperature is 750°C-850°C, the pressure is 4MPa-6MPa, and the vacuum degree is greater than or equal to 5×10 -2 Pa.

[0016] In one of the embodiments, in the step of thermal deformation treatment, the deformation amount is 65%-75%.

[0017] A heat-deformed NdFeB magnet is prepared by the heat-deformed NdFeB magnet preparation method as described above.

[0018] The preparation method of the hot-deformed NdFeB magnet of the present invention is to mix a certain amount of iron-nickel alloy powder containing nickel elements with NdFeB quick-quenching powder, so that the iron-nickel alloy powder containing nickel elements can be distributed at the Nd-Fe-B grain boundary and strip during hot pressing and hot deformation, and the easy diffusion property of nickel elements in the iron-nickel alloy powder is utilized to greatly increase the content of ferromagnetic substances at the grain boundary and in the grain of the hot-deformed NdFeB magnet, thereby enhancing the exchange coupling effect between Nd-Fe-B grains and improving the remanence and magnetic energy product of the hot-deformed NdFeB magnet. At the same time, nickel atoms can enter the Nd-Fe-B matrix and replace iron atoms, causing the lattice to change, thereby improving the mechanical processing performance of the hot-deformed NdFeB magnet and improving its practicality.

[0019] Therefore, the heat-deformed NdFeB magnet obtained by the preparation method of the present invention has higher remanence and magnetic energy product, and its magnetic properties are more excellent. In addition, the preparation process of the heat-deformed NdFeB magnet is simple and can be widely used in the actual production of heat-deformed NdFeB magnets. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The backscattering image and EDS element surface distribution image of the thermally deformed NdFeB magnet prepared in Example 1;

[0021] Figure 2 The demagnetization curves of the heat-deformed NdFeB magnets prepared in Example 1, Example 2 and Comparative Example 1 and Comparative Example 2 are shown in FIG. A is the demagnetization curve of the heat-deformed NdFeB magnet prepared in Example 1; B is the demagnetization curve of the heat-deformed NdFeB magnet prepared in Example 2; C is the demagnetization curve of the heat-deformed NdFeB magnet prepared in Comparative Example 1; and D is the demagnetization curve of the heat-deformed NdFeB magnet prepared in Comparative Example 2. DETAILED DESCRIPTION

[0022] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.

[0024] The present invention provides a method for preparing a thermally deformed NdFeB magnet, the method comprising the following steps:

[0025] S1, providing an iron-nickel alloy powder, wherein the mass fraction of nickel in the iron-nickel alloy powder is greater than or equal to 15%;

[0026] S2, providing NdFeB quick-quenching powder, mixing the NdFeB quick-quenching powder with the iron-nickel alloy powder to obtain a mixed powder, and hot pressing and hot deforming the mixed powder under vacuum conditions to obtain a hot-deformed NdFeB magnet, wherein the mass fraction of the iron-nickel alloy powder in the mixed powder is less than or equal to 3%.

[0027] In step S1, iron-nickel alloy powder is selected, and the advantage of the smaller size of nickel atoms is used to make the nickel element in the iron-nickel alloy powder more easily diffuse, thereby facilitating the coupling effect between grains.

[0028] In order to further enhance the coupling effect between grains, the mass fraction of the nickel element in the iron-nickel alloy powder is preferably 15%-28%, and more preferably 20%-28%.

[0029] In order to further improve the physical properties of the iron-nickel alloy powder, so that the iron-nickel alloy has a shape memory effect, which is beneficial to improve the rheological properties of the magnet during thermal deformation, optimize the magnet texture and thus improve the magnetic properties of the magnet, in one embodiment, the iron-nickel alloy powder also contains cobalt element, and the mass fraction of the cobalt element in the iron-nickel alloy powder is less than or equal to 20%, preferably 10%-20%, and further preferably 10%-17%.

[0030] Since the Fe-Ni alloy powder with a smaller particle size is more conducive to forming a good crystal texture, in one embodiment, the average particle size (D 50 ) is less than 5 μm, and preferably the average particle size (D 50 ) is less than 1μm.

[0031] It should be noted that in step S2, if excessive iron-nickel alloy powder is introduced, during the hot pressing and hot deformation process, the submicron iron-nickel alloy powder containing nickel elements will be enriched in the strips in large quantities, thereby limiting the formation of the crystal texture of the hot-deformed NdFeB magnet, resulting in a decrease in the magnetic properties of the hot-deformed NdFeB magnet.

[0032] Therefore, the present invention mixes a certain amount of iron-nickel alloy powder containing nickel elements with NdFeB quick-quenching powder. During the hot pressing and hot deformation process, the iron-nickel alloy powder containing nickel elements can be distributed on the Nd-Fe-B grain boundaries and strips, and the easy diffusion property of the nickel element in the iron-nickel alloy powder is utilized to greatly increase the content of ferromagnetic substances at the grain boundaries and in the grains of the hot-deformed NdFeB, thereby enhancing the exchange coupling effect between the Nd-Fe-B grains and improving the remanence and magnetic energy product of the hot-deformed NdFeB magnet.

[0033] At the same time, the nickel element contained in the iron-nickel alloy powder can also overcome the problem of uneven mixing caused by the easy agglomeration of the powder during the mixing process of the iron-nickel alloy powder and the neodymium iron boron quick-quenching powder, thereby improving the mechanical processing performance of the hot-deformed neodymium iron boron magnet and improving its practicality.

[0034] Specifically, the mass fraction of the iron-nickel alloy powder in the mixed powder is preferably 1%-3%.

[0035] Since NdFeB quick-quenching powder has a strong affinity with oxygen, the introduction of oxygen atoms will affect the rare earth elements in the NdFeB quick-quenching powder, thereby reducing the magnetic properties of the hot-deformed NdFeB magnet. Therefore, in order to avoid the introduction of oxygen atoms in the process of preparing the hot-deformed NdFeB magnet as much as possible and reduce the water content in the iron-nickel alloy powder, before the step of mixing the NdFeB quick-quenching powder with the iron-nickel alloy powder, the iron-nickel alloy powder is pretreated to remove the oxygen atoms in the iron-nickel alloy powder.

[0036] Since hot pressing and hot deformation are both carried out under vacuum conditions, and the introduction of oxygen atoms can be avoided to the greatest extent under vacuum conditions, in one embodiment, before the step of mixing the NdFeB quick-quenching powder with the iron-nickel alloy powder, the iron-nickel alloy powder can be placed under vacuum conditions for treatment and preservation, and then the iron-nickel alloy powder and the NdFeB quick-quenching powder can be directly mixed under vacuum conditions to obtain a mixed powder.

[0037] In order to fully and evenly mix the NdFeB quick-quenching powder and the Fe-Ni alloy powder, the mixing time of the NdFeB quick-quenching powder and the Fe-Ni alloy powder is preferably 15 min-30 min.

[0038] In one embodiment, the hot pressing temperature is 600°C-700°C, the pressure is 3MPa-6MPa, and the vacuum degree is greater than or equal to 5×10 -2 The thermal deformation temperature is 750°C-850°C, the pressure is 4MPa-6MPa, and the vacuum degree is greater than or equal to 5×10 -2 Pa.

[0039] It should be noted that the vacuum degree is the absolute value of the difference between the actual air pressure of the system and the external air pressure. The smaller the actual air pressure of the system is, the greater the difference between it and the external air pressure is, and the higher the vacuum degree is.

[0040] In one embodiment, during the thermal deformation process, the degree of deformation of the thermally deformed NdFeB magnet is 65%-75%.

[0041] The present invention also provides a heat-deformed NdFeB magnet prepared by the heat-deformed NdFeB magnet preparation method as described above.

[0042] The thermally deformed NdFeB magnet obtained by the preparation method of the present invention has higher remanence and magnetic energy product, and its magnetic properties are more excellent. In addition, the preparation process of the thermally deformed NdFeB magnet is simple and can be widely used in the actual production of thermally deformed NdFeB magnets.

[0043] Hereinafter, the thermally deformed NdFeB magnet and the preparation method thereof will be further described through the following specific embodiments.

[0044] Example 1

[0045] The iron-nickel-cobalt alloy powder with an average particle size of 1 μm was placed in a glove box and vacuumed, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel-cobalt alloy powder was 28%, and the mass fraction of cobalt element in the iron-nickel-cobalt alloy powder was 17%.

[0046] Weigh 29.7g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.3g of Fe-Ni-Co alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 20 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum at 5×10 -2 Pa, a temperature of 670 ° C, and an external pressure of 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5×10 -2 The thermal deformation was carried out under the conditions of 800°C, 830°C and 5MPa, and the deformation amount was about 70% to obtain a thermally deformed NdFeB magnet.

[0047] The prepared hot-deformed NdFeB magnets were subjected to element distribution tests. The test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the various elements of the Fe-Ni-Co alloy powder in the hot-deformed NdFeB magnet are evenly distributed, and no element enrichment occurs.

[0048] Example 2

[0049] The iron-nickel-cobalt alloy powder with an average particle size of 1 μm was placed in a glove box and vacuumed, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel-cobalt alloy powder was 28%, and the mass fraction of cobalt element in the iron-nickel-cobalt alloy powder was 17%.

[0050] Weigh 29.1g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.9g of Fe-Ni-Co alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 20 minutes to obtain a mixed powder. Put the mixed powder into a hot pressing mold and press it under vacuum at 5×10 -2 Pa, a temperature of 670 ° C, and an external pressure of 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5×10 -2 The thermal deformation was carried out under the conditions of 800°C, 830°C and 5MPa, and the deformation amount was about 70% to obtain a thermally deformed NdFeB magnet.

[0051] Example 3

[0052] The iron-nickel-cobalt alloy powder with an average particle size of 1 μm is placed in a glove box and vacuumized, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel-cobalt alloy powder is 15%, and the mass fraction of cobalt element in the iron-nickel-cobalt alloy powder is 20%.

[0053] Weigh 29.76g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.24g of Fe-Ni-Co alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 20 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum at 5×10 -2 Pa, a temperature of 670 ° C, and an external pressure of 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5×10 -2 The thermal deformation was carried out under the conditions of 800°C, 830°C and 5MPa, and the deformation amount was about 70% to obtain a thermally deformed NdFeB magnet.

[0054] Example 4

[0055] The iron-nickel-cobalt alloy powder with an average particle size of 1 μm is placed in a glove box and vacuumized, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel-cobalt alloy powder is 20%, and the mass fraction of cobalt element in the iron-nickel-cobalt alloy powder is 10%.

[0056] Weigh 29.55g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.45g of Fe-Ni-Co alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 20 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum at 5×10 -2 Pa, a temperature of 670 ° C, and an external pressure of 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5×10 -2 The thermal deformation was carried out under the conditions of 800°C, 830°C and 5MPa, and the deformation amount was about 70% to obtain a thermally deformed NdFeB magnet.

[0057] Example 5

[0058] An iron-nickel alloy powder with an average particle size of 4 μm is placed in a glove box and vacuumized, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel alloy powder is 50%.

[0059] Weigh 29.7g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.3g of Fe-Ni alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 25 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum degree of 6×10 -2 Pa, a temperature of 675 ° C, and an external pressure of 5 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 6×10 -2The thermal deformation was carried out under the conditions of 800°C, 835°C and 6MPa, and the deformation amount was about 60%, thereby obtaining a thermally deformed NdFeB magnet.

[0060] Example 6

[0061] An iron-nickel alloy powder with an average particle size of 4 μm is placed in a glove box and vacuumized, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel alloy powder is 15%.

[0062] Weigh 29.55g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.45g of Fe-Ni alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 25 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum at 6×10 -2 Pa, a temperature of 675 ° C, and an external pressure of 5 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 6×10 -2 The thermal deformation was carried out under the conditions of 800°C, 835°C and 6MPa, and the deformation amount was about 70% to obtain a thermally deformed NdFeB magnet.

[0063] Example 7

[0064] An iron-nickel alloy powder with an average particle size of 4 μm is placed in a glove box and vacuumized, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel alloy powder is 20%.

[0065] Weigh 29.1g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.9g of Fe-Ni alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 25 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum degree of 6×10 -2 Pa, a temperature of 675 ° C, and an external pressure of 5 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 6×10 -2 The thermal deformation was carried out under the conditions of 800°C, 835°C and 6MPa, and the deformation amount was about 70% to obtain a thermally deformed NdFeB magnet.

[0066] Comparative Example 1

[0067] Weigh 30g of NdFeB quick-quenching powder and put it into the hot pressing mold. -2 Pa, temperature 670 ° C, and external pressure 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5 × 10 -2Pa, temperature 830 ° C, external pressure 5MPa under the conditions of thermal deformation, the deformation amount is about 70%, to obtain a thermally deformed NdFeB magnet.

[0068] Comparative Example 2

[0069] The iron-nickel-cobalt alloy powder with an average particle size of 1 μm was placed in a glove box and vacuumed, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel-cobalt alloy powder was 28%, and the mass fraction of cobalt element in the iron-nickel-cobalt alloy powder was 17%.

[0070] Weigh 28.5g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 1.5g of Fe-Ni-Co alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 20 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum at 5×10 -2 Pa, temperature 670 ° C, and external pressure 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5 × 10 -2 Pa, temperature 830 ° C, external pressure 5MPa under the conditions of thermal deformation, the deformation amount is about 70%, to obtain a thermally deformed NdFeB magnet.

[0071] The element analysis of the thermally deformed NdFeB magnet is as follows: Figure 2 As shown, it can be seen that the nickel and cobalt elements in the iron-nickel-cobalt alloy powder are largely enriched in the strips, with obvious element segregation phenomenon.

[0072] Comparative Example 3

[0073] The iron-nickel-cobalt alloy powder with an average particle size of 1 μm is placed in a glove box and vacuumized, and then stored in the glove box, wherein the mass fraction of nickel element in the iron-nickel-cobalt alloy powder is 10%, and the mass fraction of cobalt element in the iron-nickel-cobalt alloy powder is 17%.

[0074] Weigh 29.1g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 0.9g of Fe-Ni-Co alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 20 minutes to obtain a mixed powder. Put the mixed powder into a hot pressing mold and press it under vacuum at 5×10 -2 Pa, temperature 670 ° C, and external pressure 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5 × 10 -2 Pa, temperature 830 ° C, external pressure 5MPa under the conditions of thermal deformation, the deformation amount is about 70%, to obtain a thermally deformed NdFeB magnet.

[0075] Comparative Example 4

[0076] The iron-cobalt alloy powder with an average particle size of 10 μm was placed in a glove box and vacuumed, and then stored in the glove box, wherein the mass fraction of cobalt element in the iron-cobalt alloy powder was 35.5%.

[0077] Weigh 28.5g of NdFeB quenching powder into a glass bottle and put it into the glove box. Weigh 1.5g of Fe-Co alloy powder in the glove box and put it into the glass bottle containing NdFeB quenching powder and shake and mix for 20 minutes to obtain mixed powder. Put the mixed powder into the hot pressing mold and press it under vacuum degree of 5×10 -2 Pa, temperature 670 ° C, and external pressure 4 MPa, hot pressing was performed to obtain a block blank; the block blank was placed in a hot deformation mold and the vacuum degree was 5 × 10 -2 Pa, temperature 830 ° C, external pressure 5MPa under the conditions of thermal deformation, the deformation amount is about 70%, to obtain a thermally deformed NdFeB magnet.

[0078] The performance of the thermally deformed NdFeB magnets prepared in Examples 1-7 and Comparative Examples 1-4 was tested. The test results are shown in Table 1 below.

[0079] Table 1

[0080]

[0081]

[0082] According to Table 1, the remanence and magnetic energy product of the hot-deformed NdFeB magnet prepared by using the iron-nickel alloy powder are significantly improved. In Example 1, when the mass fraction of the iron-nickel-cobalt alloy powder in the mixed powder is 1%, the remanence of the prepared hot-deformed NdFeB magnet reaches 14.38kG, and the magnetic energy product is 49.71MGoe. Compared with the hot-deformed NdFeB magnet prepared by the comparative example 1 without adding the iron-nickel alloy powder, the remanence of the hot-deformed NdFeB magnet of Example 1 is increased by about 5%, and a certain coercive force can be maintained.

[0083] The hot-deformed NdFeB magnets prepared in Example 1-2 and Comparative Example 1-2 were subjected to magnetization tests. The test results are as follows: Figure 2 As shown. Figure 2 From the demagnetization curve shown, it can be further clearly observed that the remanence of the hot-deformed NdFeB magnet prepared with 1% Fe-Ni-Co alloy powder is the best, while the remanence of the hot-deformed NdFeB magnet prepared without adding Fe-Ni alloy powder and the hot-deformed NdFeB magnet prepared with 5% Fe-Ni-Co alloy powder are poor.

[0084] In Comparative Example 3, due to the low mass fraction of nickel in the iron-nickel-cobalt alloy powder, the diffusion effect is not as good as that in Examples 1-2, resulting in reduced magnetic properties of the hot-deformed NdFeB magnet. In Comparative Example 4, hot-deformed NdFeB magnets were prepared by mixing iron-cobalt alloy powder with NdFeB quenching powder. Obviously, the magnetic properties of the hot-deformed NdFeB magnets are lower than those of the hot-deformed NdFeB magnets prepared in Examples 1-7.

[0085] In summary, the thermally deformed NdFeB magnet obtained by the preparation method of the present invention can effectively improve the remanence and magnetic energy product of the thermally deformed NdFeB magnet, thereby optimizing the magnetic properties of the thermally deformed NdFeB magnet.

[0086] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a thermally deformed NdFeB magnet, characterized in that: The preparation method comprises the following steps: Providing an iron-nickel alloy powder, wherein the mass fraction of nickel in the iron-nickel alloy powder is 15%-28%, and the iron-nickel alloy powder further contains a cobalt element, and the mass fraction of the cobalt element in the iron-nickel alloy powder is 10%-20%; and Provide NdFeB quick-quenching powder, mix the NdFeB quick-quenching powder with the iron-nickel alloy powder to obtain a mixed powder, and perform hot pressing and hot deformation treatment on the mixed powder under vacuum conditions to obtain a hot-deformed NdFeB magnet, wherein the mass fraction of the iron-nickel alloy powder in the mixed powder is less than or equal to 3%, the hot pressing pressure is 3MPa-6MPa, and the hot deformation pressure is 4MPa-6MPa.

2. The method for preparing a thermally deformed NdFeB magnet according to claim 1, characterized in that: The mass fraction of the cobalt element in the iron-nickel alloy powder is 10%-17%.

3. The method for preparing a thermally deformed NdFeB magnet according to claim 1, characterized in that: The mass fraction of the nickel element in the iron-nickel alloy powder is 20%-28%.

4. The method for preparing a thermally deformed NdFeB magnet according to claim 1, characterized in that: The mass fraction of the iron-nickel alloy powder in the mixed powder is 1%-3%.

5. The method for preparing a thermally deformed NdFeB magnet according to claim 1, characterized in that: The average particle size of the iron-nickel alloy powder is less than 5 μm.

6. The method for preparing a thermally deformed NdFeB magnet according to claim 1, characterized in that: Before the step of mixing the NdFeB quenching powder with the Fe-Ni alloy powder, the Fe-Ni alloy powder is subjected to a deoxidation pretreatment.

7. The method for preparing a thermally deformed NdFeB magnet according to claim 1, characterized in that: The hot pressing temperature is 600°C-700°C, and the vacuum degree is greater than or equal to 5×10 -2 Pa; And / or, the thermal deformation temperature is 750°C-850°C, and the vacuum degree is greater than or equal to 5×10 -2 Pa.

8. The method for preparing a thermally deformed NdFeB magnet according to claim 1, characterized in that: In the step of thermal deformation treatment, the deformation amount is 65%-75%.

9. A hot-deformed NdFeB magnet prepared by the method for preparing a hot-deformed NdFeB magnet as claimed in any one of claims 1 to 8.